Komparasi Efektivitas Microlearning Berbasis Tiktok dengan Metode Pembelajaran Lecturing dalam Pembelajaran Bahasa Inggris - Ni Made Sri Rahayu; Ni Luh Supartini - (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to compare the effectiveness of TikTok-based microlearning with the lecturing method in English learning for 3rd semester students of the Diploma III Hospitality program at the Institute of Tourism and International Business. The purpose of this research is to overcome the challenges of low motivation to learn and vocabulary mastery in conventional English learning, especially in Generation Z students who are familiar with digital technology. By utilizing the TikTok as a microlearning, this study explores a short and contextual video content can significantly improve learning outcomes compared to traditional lecture methods. The study used a quasi-experimental design with 60 students divided into an experimental group (TikTok) and a control group (lecturing). The intervention was carried out for six weeks with English material for hospitality. Data were collected through pre-tests and post-tests of vocabulary mastery, speech ability assessments, learning motivation questionnaires (ARCS model), and participatory observation. The results showed that the experimental group experienced a significant increase in vocabulary mastery (28%,p < 0.001) and learning motivation (35%, p < 0.001) compared to the control group (15% and 12%). However, no significant differences were found in speaking ability (p=0.12), suggesting that microlearning needs to be combined with active exercise for productive skills. Research limitations include short duration, samples from one institution, and non-randomized assignments. Nonetheless, these findings support the integration of TikTok-based microlearning as an effective additional learning tool in improving vocabulary retention and student engagement in vocational education.